CONTRASTING STYLES OF CONVERGENCE IN THE ARABIA-EURASIA COLLISION: WHY ESCAPE TECTONICS DOES NOT OCCUR IN IRAN - Allen M.B.; Blanc E.J.-P.; Walker R.; Jackson J.; Talebian M.; Ghassemi M.R. (My University, 2006)
The westward motion of Turkey relative to Eurasia between the North and East Anatolian faults has been cited as one of the best examples of lateral transport of continental crust from a collision zone, in this case the Arabia-Eurasia collision. This process is variously called "escape" or "extrusion" tectonics. Range-parallel strikeslip faults within the Alborz (e.g., the Mosha fault) and Zagros Mountains (the Main Recent fault) of Iran have been regarded as playing roles similar to those of the North and East Anatolian faults in that they are responsible for the eastward transport of intervening Iranian crust away from the northward motion of the Arabia plate relative to Eurasia. However, both seismicity and GPS data show that there is no net eastward transport of Iranian crust with respect to Eurasia. Here we summarize how the tectonically active mountain ranges of Iran deform by combinations of thrusting and strike-slip movement oblique to the overall convergence vector across each region, without requiring net eastward movement with respect to Eurasia. A general conclusion is that strike-slip faults in collision zones can have different roles. These include not only the lateral transport of crustal material demonstrated in Turkey, but also the partitioning of strain into shortening and strike-slip components shown by the Alborz and Zagros structures and the accommodation of crustal shortening by strike-slip faults that rotate about a vertical axis. © 2006 Geological Society of America.
Keywords: ARABIA; COLLISION; ESCAPE TECTONICS; EURASIA